2008
DOI: 10.1111/j.1440-172x.2008.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Automated versus manual blood pressure measurement: A randomized crossover trial

Abstract: This study evaluated the accuracy and reliability of the Dinamap 8100 automated blood pressure machine against three internationally recognized criteria. Systolic and diastolic blood pressures were taken concurrently by two nurses using the automated machine and a manual sphygmomanometer. Results demonstrated agreement between automated and manual readings on one set of criteria for both systolic and diastolic pressures, and support for systolic readings only on one other criterion. Comparison of mean differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 15 publications
2
10
0
1
Order By: Relevance
“…SBP showed a mean difference of 15.32±1. 25 [18]. The results were in concordance with ours, as it showed high values of SBP recorded by automated instrument [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…SBP showed a mean difference of 15.32±1. 25 [18]. The results were in concordance with ours, as it showed high values of SBP recorded by automated instrument [19].…”
Section: Discussionsupporting
confidence: 91%
“…Automated device is used for BP estimation in day-to-day clinical practice in multiple settings such as outpatient, critical care, and continuous BP monitoring. Critical decision and pharmacological interventions are done based on this parameter [25,26]. We observed from our results that there is a higher value of recorded BP with automated device, especially in hypertensives.…”
Section: Resultsmentioning
confidence: 64%
“…For blood pressure, we focused on results for SBP since it is a better predictor of long term outcomes (20) and is more accurately measured than DBP (21). Biomarkers that were not normally distributed (triglycerides, HOMA-IR, CRP, and IL-6) were natural log-(ln)-transformed prior to use in the regression models.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is important that all nurses are skilled in performing manual BP measurement. Heinemann et al (2008) found that automated BP measurement devices can be used with some confidence to record systolic BP in most adults, but there was some variation observed when recording diastolic BP.…”
Section: Evidence Basementioning
confidence: 99%